Asporin-deficient mice have tougher skin and altered skin glycosaminoglycan content and structure. - Marco Maccarana; René B Svensson; Anki Knutsson; Antonis Giannopoulos; Mea Pelkonen; MaryAnn Weis; David Eyre; Matthew Warman; Sebastian Kalamajski (PLoS ONE)
The main structural component of connective tissues is fibrillar, cross-linked collagen whose fibrillogenesis can be modulated by Small Leucine-Rich Proteins/Proteoglycans (SLRPs). Not all SLRPs' effects on collagen and extracellular matrix in vivo have been elucidated; one of the less investigated SLRPs is asporin. Here we describe the successful generation of an Aspn-/- mouse model and the investigation of the Aspn-/- skin phenotype. Functionally, Aspn-/- mice had an increased skin mechanical toughness, although there were no structural changes present on histology or immunohistochemistry. Electron microscopy analyses showed 7% thinner collagen fibrils in Aspn-/- mice (not statistically significant). Several matrix genes were upregulated, including collagens (Col1a1, Col1a2, Col3a1), matrix metalloproteinases (Mmp2, Mmp3) and lysyl oxidases (Lox, Loxl2), while lysyl hydroxylase (Plod2) was downregulated. Intriguingly no differences were observed in collagen protein content or in collagen cross-linking-related lysine oxidation or hydroxylation. The glycosaminoglycan content and structure in Aspn-/- skin was profoundly altered: chondroitin/dermatan sulfate was more than doubled and had an altered composition, while heparan sulfate was halved and had a decreased sulfation. Also, decorin and biglycan were doubled in Aspn-/- skin. Overall, asporin deficiency changes skin glycosaminoglycan composition, and decorin and biglycan content, which may explain the changes in skin mechanical properties.